(untitled) (Western European Journal of Historical Events and Social Science, 2025)
This study examines the scholars and scientific activities during the Khwarazmshah period, highlighting the role of madrasas, the contributions of prominent scholars, and the development of Islamic education in the region. It analyzes how state patronage, social support, and religious values fostered intellectual growth and shaped the educational landscape. The study also emphasizes the architectural, organizational, and educational aspects of the madrasas, their role in promoting jurisprudence, theology, and other sciences, and their influence on society. By exploring historical documents and scholarly sources, the research provides a comprehensive overview of the intellectual life and scientific advancements in the Khwarazmshah era